Adaptive-Fuzzy-PID Controller Based Disturbance Observer for DC Motor Speed Control - Zulfatman Has; Ahzen Habibidin Muslim; Nur Alif Mardiyah (IAES Indonesia Section, 2017)
DC motors are one of the most widely used actuators in industry applications. In its use, the reliability of DC motor performance becomes an important prerequisite that must be met. Therefore, a control scheme is required to meet the above performance demands, especially in the transient, steady state, and system stability aspects. The main problems in DC motor control system, especially in terms of speed control, are the occurrence of changes in system parameters and the presence of disturbances such as load changes. This study offers an Adaptive- Fuzzy-PID (AFPID) control scheme equipped with Disturbance Observer (DOb). AFPID scheme plays a role in handling the change of system parameters, while DOb serves to estimate the occurrence of disturbance. The AFPID control scheme was verified experimentally on a DC motor test-rig that was subjected to load-bearing disturbance. The results of the experiments show that the AFPID control scheme with DOb has a better transient response performance than AFPID without DOb, as well as in the ability to compensate the load changes. The combination of AFPID with DOb offers a more stable performance to DC motor has and is more insensitive to disturbance.